Performance evaluation of grid-following and grid-forming inverters on frequency stability in low-inertia power systems by power hardware-in-the-loop testing - Hiroshi Kikusato; Dai Orihara; Jun Hashimoto; Takahiro Takamatsu; Takashi Oozeki; Takahiro Matsuura; Satoshi Miyazaki; Hiromu Hamada; Teru Miyazaki (Energy Reports, 2023)
Developing advanced control functions for inverter-based resources (IBRs) to replace the inertial response of retiring synchronous generators (SGs) is progressing rapidly. Although various control mechanisms have been proposed for grid-following (GFL) inverters and grid-forming (GFM) inverters, the comprehensive comparison of their performance in contributing to grid stabilization based on hardware testings has not been studied well. This paper performs power hardware-in-the-loop (PHIL) testing for multiple inverter prototypes from different manufacturers and compares their performance concerning the difference in inverter types, control methods, and IBR penetration conditions in the power system. It also tests the possible interference between islanding detection methods (IDMs) and frequency control capabilities of GFL and GFM inverters.